Progressive Disseminated Histoplasmosis in an Immunocompetent Host: A Rare Presentation of an Uncommon Disease - Agarwal, Mehul; Gupta, Manohar Lal; Shadrach, Benhur Joel; Bharti, Neha (Acta Biomedica Atenei Parmensis, 2021)
Disseminated Histoplasmosis, a systemic fungal infection caused by Histoplasma capsulatum is predominantly seen in immunocompromised cases. It is usually endemic, although sporadic cases have been reported. Following initial infection to the lungs, it disseminates to various organs by lymphatic and hematogenous routes. Clinical features are non-specific and depend on the extent and severity of organ involvement. A Biopsy is required for diagnosis and timely intervention decreases morbidity and mortality. Our case report describes an atypical association of progressive disseminated Histoplasmosis with bone marrow involvement in an immunocompetent adult from a non-endemic region and alerts the clinicians to a rare yet life-threatening mycosis.